Strengthening Sharia Economics in Jayapura's Muslim Minority Communities through Fiqh al-Aqalliyyat - Jubaedah, Dedah; Solehudin, Ending; Berizi, Ahmad; Mutakin, Ali; Nurhasana, Nurhasana; Parhan, Parhan; Gómez, José Manuel Naranjo (IAIN Manado, 2025)
The Muslim community in Jayapura faces significant challenges in implementing Sharia-based economics, chiefly due to persistent social stigma surrounding halal products and limited public understanding of Islamic economic principles. This study explores how Fiqh al-Aqalliyyat a flexible jurisprudential framework can address these challenges within a multicultural society. Adopting a qualitative case study methodology, the research draws on interviews with 14 key local stakeholders, including government officials, religious leaders, and business owners. Data were gathered through purposive sampling and analyzed thematically to identify key barriers and viable solutions. The findings indicate that social stigma and inadequate infrastructure impede halal product promotion. Nevertheless, significant opportunities exist, including a growing demand for halal goods, government support for Sharia-compliant capital markets, and the active engagement of religious institutions. The novelty of this research lies in its integration of Fiqh al-Aqalliyyat and Maqasid al-Sharia as analytical frameworks to address the specific socio-economic realities of a Muslim minority in Jayapura, offering practical insights applicable to similar contexts elsewhere.The Muslim community in Jayapura faces significant challenges in implementing Sharia-based economics, chiefly due to persistent social stigma surrounding halal products and limited public understanding of Islamic economic principles. This study explores how Fiqh al-Aqalliyyat a flexible jurisprudential framework can address these challenges within a multicultural society. Adopting a qualitative case study methodology, the research draws on interviews with 14 key local stakeholders, including government officials, religious leaders, and business owners. Data were gathered through purposive sampling and analyzed thematically to identify key barriers and viable solutions. The findings indicate that social stigma and inadequate infrastructure impede halal product promotion. Nevertheless, significant opportunities exist, including a growing demand for halal goods, government support for Sharia-compliant capital markets, and the active engagement of religious institutions. The novelty of this research lies in its integration of Fiqh al-Aqalliyyat and Maqasid al-Sharia as analytical frameworks to address the specific socio-economic realities of a Muslim minority in Jayapura, offering practical insights applicable to similar contexts elsewhere.